Sewage Effluent Causes Metal Pollution of a Sub-tropical River System in Zimbabwe - Dube, T.; Chibanda, M.; Manhire, B.; Rutanhira, C.; Mabugu, C.; Makaka, C.; Makaure, J.; Muteveri, T. (Springer, 2021)
Metal pollutants are persistent in the environment and of concern to human health. The aim of the study was to assess the distribution of metals (Cr, Fe, Pb, Mg and Cu) in Sebakwe River. Water and sediment samples were collected from upstream reference sites (4 and 5) and influenced downstream sites (1, 2 and 3) of the sewage effluent discharge point. Pb concentrations in water were significantly higher (p < 0.05) in sites 1 and 2 downstream of the sewage discharge point. In the sediments, the sites downstream of the effluent discharge point had significantly higher concentrations of Cu (p < 0.05) and Cr (p < 0.05). A comparison of metal concentration in water with World Health Organization and Standards Association of Zimbabwe standards revealed that the levels of Pb in water were above the recommended limits, posing a health risk to Pb poisoning for people living along Sebakwe River.